Russian Philosophers on Personal Origins Social Concepts - V. B. Aleksandrov (Управленческое консультирование, 2022)
The article examines the personal-psychological approach of Russian philosophers to understanding the content of social concepts. In particular, attention is drawn to the attempt of M. A. Bakunin and S. N. Bulgakov to show the conditionality of K. Marx’s teachings about the dictatorship of the proletariat with the characteristic features of his personality. The idea is expressed that the views of Bakunin himself are largely due to the features of his personality. The article also discusses a more general provision on the importance of the approach from the point of view of human nature in understanding the vitality of general sociological ideas. As an example of the application of this approach, Bakunin’s criticism of the idea of the dictatorship of the proletariat, based on his idea of the natural motivation of human behavior in specific life circumstances, is considered. The author concludes that psychological interpretation can complement the sociological construction in terms of its conformity with human nature, characteristic of it system of behavioral motivation. In addition, personal-psychological justification allows us to look at political or sociological concepts as cultural phenomena that explicitly or implicitly contain certain value attitudes.